Influence of the temperature on the nucleation of silver nanoparticles in Tm3+/Yb3+ codoped PbO-GeO2 glasses - de Assumpcao, T. A. A.; da Silva, D. M.; Kassab, L. R P [UNESP]; Martinelli, J. R.; de Araujo, C. B. (Elsevier B.V., 2010)
The influence of the temperature on the nucleation of silver nanoparticles (NPs) in Tm3+/Yb3+ codoped PbO-GeO2 glasses was studied in this work. The infrared-to-visible frequency upconversion (UC) luminescence of Tm3+ ions was used to probe the NPs nucleation and the results were correlated with the increase of the heat-treatment temperature. Emission spectra in the blue-red region were measured by exciting the samples with a cw 980 nm diode laser in resonance with the Yb3+ transition (F-2(7/2) -> F-2(5/2)). The results were correlated with transmission electron microscopy measurements and revealed the different behavior of the nucleation process as a function of temperature.The enhanced UC emission in the visible region is attributed to the increased local field in the proximity of the silver NPs combined with the Yb3+ -> Tm3+ energy transfer. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Nanoparticles; Upconversion; Lead germanate glass